Engineered Electron‐Transfer Chain in Photosystem 1 Based Photocathodes Outperforms Electron‐Transfer Rates in Natural Photosynthesis. Issue 35 (25th July 2014) - Kothe, Tim; Pöller, Sascha; Zhao, Fangyuan; Fortgang, Philippe; Rögner, Matthias; Schuhmann, Wolfgang; Plumeré, Nicolas
Abstract Photosystem 1 (PS1) triggers the most energetic light‐induced charge‐separation step in nature and the in vivo electron‐transfer rates approach 50 e− s−1 PS1−1. Photoelectrochemical devices based on this building block have to date underperformed with respect to their semiconductor counterparts or to natural photosynthesis in terms of electron‐transfer rates. We present a rational design of a redox hydrogel film to contact PS1 to an electrode for photocurrent generation. We exploit the pH‐dependent properties of a poly(vinyl)imidazole Os(bispyridine)2Cl polymer to tune the redox hydrogel film for maximum electron‐transfer rates under optimal conditions for PS1 activity. The PS1‐containing redox hydrogel film displays electron‐transfer rates of up to 335±14 e− s−1 PS1−1, which considerably exceeds the rates observed in natural photosynthesis or in other semiartificial systems. Under O2 supersaturation, photocurrents of 322±19 μA cm−2 were achieved. The photocurrents are only limited by mass transport of the terminal electron acceptor (O2). This implies that even higher electron‐transfer rates may be achieved with PS1‐based systems in general.